Teaching large-enrollment online language courses: Faculty perspectives and an emerging curricular model. (April 2022) - Bikowski, Dawn; Park, H. Keira; Tytko, Tetiana
Abstract: Large enrollment online courses (over 40 students) are becoming increasingly common due to the profits they can offer institutions. Little research, however, has been conducted into faculty experiences in these contexts. This qualitative study fills this need and explores the experiences, challenges, and strategies of faculty, specifically in courses that have traditionally required interaction between students and teachers. Participants were professors and administrators ( N  = 13) of Chinese, English, Japanese, and Spanish teaching in a South Korean cyber university. Data included an online survey, interviews, and document analysis. Participants reported feeling slightly more-favorable than less-favorable about their experiences teaching and their students' experiences learning in these courses. ACTFL's (2010) guidelines for language courses were re-examined considering the current technology and budgetary environment, with findings ultimately leading to the Framework for Developing and Teaching Large Online Language Courses . We offer an expansion of the ACTFL criteria of meaningful interaction, documenting the role that interaction between student and rich media content has to offer. This study also highlights the degree to which these large online courses rely on students arriving with their own self-directed learning strategies, underlining concerns related to equity in education.